Factors associated with the effectiveness and reach of NHS Stop Smoking Services for pregnant women in England - Vaz, Luis R.; Coleman, Tim; Fahy, Samantha; Cooper, Sue; Bauld, Linda; Szatkowski, Lisa (BioMed Central, 2017)
Background